Synergistic antitumour activity of RAF265 and ZSTK474 on human TT medullary thyroid cancer cells. Issue 9 (17th June 2015) - Bertazza, Loris; Barollo, Susi; Radu, Claudia Maria; Cavedon, Elisabetta; Simioni, Paolo; Faggian, Diego; Plebani, Mario; Pelizzo, Maria Rosa; Rubin, Beatrice; Boscaro, Marco; Pezzani, Raffaele; Mian, Caterina
Abstract: Medullary thyroid cancer (MTC) is an aggressive malignancy responsible for up to 14% of all thyroid cancer‐related deaths. It is characterized by point mutations in the rearranged during transfection ( RET ) proto‐oncogene. The activated RET kinase is known to signal via extracellular signal regulated kinase (ERK) and phosphoinositide 3‐kinase (PI3K), leading to enhanced proliferation and resistance to apoptosis. In the present work, we have investigated the effect of two serine/threonine‐protein kinase B‐Raf (BRAF) inhibitors (RAF265 and SB590885), and a PI3K inhibitor (ZSTK474), on RET‐mediated signalling and proliferation in a MTC cell line (TT cells) harbouring the RETC634W activating mutation. The effects of the inhibitors on VEGFR2, PI3K/Akt and mitogen‐activated protein kinases signalling pathways, cell cycle, apoptosis and calcitonin production were also investigated. Only the RAF265+ ZSTK474 combination synergistically reduced the viability of treated cells. We observed a strong decrease in phosphorylated VEGFR2 for RAF265+ ZSTK474 and a signal reduction in activated Akt for ZSTK474. The activated ERK signal also decreased after RAF265 and RAF265+ ZSTK474 treatments. Alone and in combination with ZSTK474, RAF265 induced a sustained increase in necrosis. Only RAF265, alone and combined with ZSTK474, prompted a significant drop in calcitonin production. Combination therapy using RAF265 and ZSTK47 proved effective in MTC, demonstrating a cytotoxic effect. As the two inhibitors have been successfully tested individually in clinical trials on other human cancers, our preclinical data support the feasibility of their combined use in aggressive MTC.